Investigating the Essence of Organizational Identity: Perspectives from Employees in the Banking Sector of Nepal - Thapa, Anu; Pokharel, Bal Singh; Acharya, Arjun Kumar (Nepal Journal of Multidisciplinary Research, 2023)
This study pursued to examine employees' perceptions of organizational identity in different banks within the Nepalese banking industry and to identify the relationship between perceptions of organizational identity on demographic factors. To define the features and pinpoint the relationship, the descriptive research design is used for the study. A total of 228 employees were chosen to investigate the findings of this study. The survey included just the banks in the Kathmandu district. Questionnaires with Likert scales were employed as data collection techniques, and mean, standard deviation, and correlation were utilized to analyze the data. SPSS was used to investigate the outcome. Employee perceptions of organizational identity in the Nepalese banking industry vary widely, reflecting diverse levels of personal attachment and identification. Demographic factors like gender, marital status, and age do not significantly impact these perceptions, indicating consistency across different employee groups. This underscores the importance of recognizing individual differences while understanding that organizational identity remains stable and consistent within the industry. Organizations can use this knowledge to enhance employee engagement and foster a sense of identity, contributing to overall success. In conclusion, Nepalese banking employees share a common organizational identity despite their diverse individual perceptions.